A Comparative Clinical Study to Evaluate the Effect of Haritakyadi Kwatha and Eladi Churna in the Management of Pittaj Mutrakrichha w.s.r. to Urinary Tract Infection (AYUSHDHARA, 2023)
Mutrakrichha is a disorder of Mutravahastrotas, The term ‘Mutrakrichha’ means pain and difficulty during passage of urine. Vitiated Pitta and Pratiloma Gati of Apana Vayu are considered to be the two major factors for the pathogenesis of the disease “Mutrakrichha”. The symptoms of Pittaj Mutrakrichha such as Saruja/Krichha Mutrapravrutti (dysuria), Sarakta Mutrata (haematuria), Sadaha Mutrata (burning micturition), Muhurmuhu Mutrapravrutti (increased frequency or urgency of micturition) are coincide with the symptoms of lower urinary tract infection. Clinical presentation of Pittaj Mutrakṛichha shows close resemblance to UTI's as described in modern texts especially with lower urinary tract infections i.e., Urethritis and Cystitis. Globally UTI affect 150 million people worldwide annually. Urinary tract infection is a broad term that encompasses both asymptomatic microbial colonization of the urine and symptomatic infection with microbial invasion and inflammation of urinary tract. E.coli is the most common causative organism to cause UTI. 32 patients who were diagnosed with Pittaj Mutrakrichha w.s.r to urinary tract infection were allocated randomly into two groups. The trial drugs i.e., Haritakyadi Kwatha 50ml was given to 16 patients of group-I and Eladi Churna 3gm was given to 16 patients of group-II for duration of 4 weeks.